2016
DOI: 10.7717/peerj.2017
|View full text |Cite
|
Sign up to set email alerts
|

The genome and transcriptome ofPhalaenopsisyield insights into floral organ development and flowering regulation

Abstract: The Phalaenopsis orchid is an important potted flower of high economic value around the world. We report the 3.1 Gb draft genome assembly of an important winter flowering Phalaenopsis ‘KHM190’ cultivar. We generated 89.5 Gb RNA-seq and 113 million sRNA-seq reads to use these data to identify 41,153 protein-coding genes and 188 miRNA families. We also generated a draft genome for Phalaenopsis pulcherrima ‘B8802,’ a summer flowering species, via resequencing. Comparison of genome data between the two Phalaenopsi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 46 publications
0
26
0
Order By: Relevance
“…Recent studies with Phalaenopsis equestris genome sequencing [57], with 2n = 2x = 38 and 29,431 predicted protein-coding genes and Phalaenopsis Brother Spring Dancer 'KHM190' [58], 2n = 2x = 38 and 41,153 protein coding genes, make room for further detailed studies on the identification and expression of genes involved in the production of PLBs from different types of somatic tissue in orchids, which can be compared with other model species and in which the embryogenic pathway is already better elucidated, similar to the studies already carried out that brought new discoveries about flowering and the development of floral organs [58].…”
Section: Genus Phalaenopsis and Relatedmentioning
confidence: 99%
“…Recent studies with Phalaenopsis equestris genome sequencing [57], with 2n = 2x = 38 and 29,431 predicted protein-coding genes and Phalaenopsis Brother Spring Dancer 'KHM190' [58], 2n = 2x = 38 and 41,153 protein coding genes, make room for further detailed studies on the identification and expression of genes involved in the production of PLBs from different types of somatic tissue in orchids, which can be compared with other model species and in which the embryogenic pathway is already better elucidated, similar to the studies already carried out that brought new discoveries about flowering and the development of floral organs [58].…”
Section: Genus Phalaenopsis and Relatedmentioning
confidence: 99%
“…Recently, the roles of B-and E-class MADS-box genes were revealed for orchid tepal development (Tsai et al, 2004;Tsai et al, 2005;Lu et al, 2007;Hsieh et al, 2013a;Su et al, 2013b;Pan et al, 2014;Hsu et al, 2015b;Huang et al, 2015;Huang et al, 2016). We have shown that knock-down expression of Eclass PeSEP1-4 genes reduced the expression of PeERF1.…”
Section: Peerf1 As a Downstream Target Of Floral Morphogenesis Genesmentioning
confidence: 99%
“…In our previous study, we examined sequencing and quality checking of Phalaenopsis, and construction of draft genome (Huang et al, 2016). Here explained briefly, to sequence the Phalaenopsis genome from extracted DNA, we applied nextgeneration sequencing technologies using the Illumina HiSeq 2000 platform.…”
Section: Sequencing Quality Control and Draft Genome Constructionmentioning
confidence: 99%
“…In our previous report, we explained about sequence assembly and dataset annotation (Huang et al, 2016). Here we performed whole-genome assembly using Velvet (https://www.ebi.ac.uk/~zerbino/velvet/) (Zerbino et al, 2008) with K-mer 63.…”
Section: De Novo Assembly and Dataset Annotationmentioning
confidence: 99%
See 1 more Smart Citation